Migrated coil expectorated 12 years after embolization of pulmonary arteriovenous malformation, due probably to abscess formation around the coil. (2020) - Konno-Yamamoto, Aya; Yamamoto, Shota; Suzuki, Junko; Fukami, Takeshi; Kitani, Masashi; Matsui, Hirotoshi
Abstract: Pulmonary arteriovenous malformations (PAVMs) are rare vascular structures providing direct capillary-free communications between pulmonary arteries and veins. Embolotherapy is indicated as a front-line therapy. We report an unusual long-term complication of coil embolization for a 44-year-old woman with hereditary hemorrhagic telangiectasia (HHT) who had repeatedly undergone the procedures for her PAVMs. She expectorated the coil which had been placed 12 years earlier and migrated to the bronchus according to the chest radiogram and bronchoscopy. Histology of the resected lung segment suggested the cavity communicating with the bronchus was the consequence of abscess formation around the coils. Even after technically successful embolization to PAVMs, long term follow-up should be necessary paying attention to the symptoms and imaging to avoid massive hemoptysis and subsequent emergency surgery.